Ficus lasiosyce (Moraceae), una nueva especie del subgénero Urostigma en el Neotrópico - González Ramírez, José; Poveda Álvarez, Luis (Lankesteriana: International Journal on Orchidology, 2016)
A new species of Ficus L. (Moraceae) restricted to the Osa Peninsula of Costa Rica is described and illustrated in this paper: Ficus lasiosyce is distinguished by the paired and sessile syconia, densely cov- ered by woolly, light brown or light golden tricomes; two basal bracts that cover almost the entire sycone are usually divided into 3-4 lobes; and by its persistent stipules exceeding the length of the syconia. It is compared to Ficus brevibracteata Burger, from Nicaragua to Colombia and Ecuador, with inconspicuous basal bracts.